Development of Communication Media, Information, and Education on Safe, Comfortable, and Healthy Bicycle Movements - Siti Nurrochmah; Arief Darmawan; Ittaqwa Ittaqwa (Universitas Riau, 2024)
The objective of developing a smartphone product in the form of the Edu-Touch application for sepak takraw learning materials as teaching material is to enhance the effectiveness and efficiency of the learning process, research, and development method (research & development) this uses the 4D model and approach put forward by Thiagarajan, which consists of 4 levels: analysis, design, development, implementation. The respondents used in this research were all 6 PJOK teachers and 80 students from two schools, namely SMPN 1 Paciran and SMPN 1 Brondong. The instrument used in this research used a questionnaire which was prepared to test validity and reliability. The percentage of experts is 96% learning experts, 88% by material experts, and 80% media experts, so the development product is valid/fit for use. In the effectiveness test in small groups and large groups, the values obtained were 81.25% and 79.78%, so the effectiveness of the development product was classified as good. The results of the analysis of small group and field group test data were 81.25% and 80.10%, in this case, the development product was included in the very feasible category. So in this research the conclusion is drawn that the application is very suitable for the use of edu-touch for smartphone-based sepak takraw material for junior secondary education unit level.